Effect of Interest Rate, Dividend per Share, Current Ratio, Debt to Equity Ratio, and Return on Asset on Stock Price with Earning per Share as Moderating Variable in Food and Beverage Companies Listed on the Indonesia Stock Exchange - Lumbanbatu, Gabriella A; Nasution, Abdillah Arif; Adnan, Aulia (Budapest International Research and Critics University, 2022)
This study aims to determine effect of interest rate, dividend per share, current ratio, debt to equity ratio, and return on asset on stock price with earning per share as moderating variable in food and beverage companies listed on the Indonesia Stock Exchange. The population use in this study is 72 Food and Beverage Companies Listed on the Indonesia Stock Exchange. The sampling method is by using non probability sampling. Data processing is carried out by means of SPSS statistical program. The results of this study indicate that: (1)interest rate has a positive and significant effect on stock price, (2)dividend per share has a positive and significant effect on stock price, (3)current ratio has no effect on stock price, (4)debt to equity ratio has no effect on stock price, (5)return on asset has a positive and significant effect on stock price, (6)earning per share is able to moderate effect of interest rate on stock price, (7)earning per shareis is not able to moderate effect of dividend per share on stock price, (8)earning per share is not able to moderate effect of current ratio on stock price, (9)earning per share is not able to moderate effect of debt to equity ratio on stock price, (10) earning per share is not able to moderate effect of return on asset on stock price.